Are we practising defensive medicine: a cure that is costlier than the disease? - Joshi, Arbin (Journal of Patan Academy of Health Sciences, 2015)
Introductions: In the current scenario where intimidation and manhandling to health personnel and vandalism in the hospital is high, sense of insecurity among the newer lot of surgeons and methods they incorporate to combat the possible threat from the patients or their peers has not been validated properly yet. Methods: A preformed questionnaire with ten yes or no answers was circulated manually or via emails among the surgical residents and surgeons of less than 5 year experience. More number of 'yes' answers was considered as high level of sense of insecurity. Results: Majority (n= 45, 90%) of respondents had 5 or more than 5 'yes' answers in the questionnaire and median 'yes' answer in the questionnaire was 8, indicating high level of insecurity among the respondents. All respondents (100%) expect themselves to be intimidated or sued in their career and 60 percent of respondents admit themselves ordering more tests than required to be on the 'safe' side. Conclusions: This study has showed both sense of insecurity and subjective prevalence of defensive medicine among the newer lot of surgeons are high.Journal of Patan Academy of Health Sciences, Vol. 2, No. 2, 2015, page: 3-6